A New Puzzle About Aristotelian Accidents. (31st August 2021) - Huismann, Tyler
I present a new puzzle that concerns Aristotle's accidents. This puzzle arises when applying a basic requirement of accidentality to the variety of cases Aristotle provides. In short, Aristotle seems to offer, now the thought that a is accidental to b, and now that b is accidental to a; but if accidentality is asymmetric, as it seems to be, then a's being accidental to b implies that b is not accidental to a. One might offer a schooled Aristotelian solution, allowing that while a is in a sense accidental to b, b is accidental to a in a quite different sense. But, as I will argue, this solution does not work, for there are cases in which a and b are accidental to each other in the same sense. Ultimately, the solution to the new puzzle relies not on distinguishing between senses of 'accident, ' but rather on unearthing a new feature of accidentality: accidentality is contextual, in a sense to be defined in the paper.